Mindset FIRE dan digital financial inclusion sebagai penentu stabilitas keuangan Generasi Z - Detak Prapanca; Nur Ravita Hanun; Putri Ayunda Anggraeni; Amelia Fitri Agustin (Universitas Kristen Maranatha, 2026)
This​‍​‌‍​‍‌​‍​‌‍​‍‌ research investigates how the FIRE mindset and digital financial inclusion impact financial stability among Generation Z, with self-concept serving as the mediating variable. The study employed a quantitative survey method and gathered data from 300 digitally active respondents. The data were then analyzed using PLS-SEM. The findings reveal that both the FIRE mindset and digital financial inclusion are significant factors that determine financial stability. Also, self-concept is a direct influencing factor of financial stability. On the contrary, digital financial inclusion neither affects self-concept significantly nor does self-concept mediate the relationships. Hence, the results point out that the behavioral discipline and long-term financial orientation of Generation Z drive their financial stability more than the psychological mediation mechanisms. The paper further explains that for improving financial resilience, financial literacy, digital access, and consistent financial behavior need to be ​‍​‌‍​‍‌​‍​‌‍​‍‌combined.